Assessment of the ecological state of Kazan surface waters - A. M. Shakirzyanov; D. I. Petrova; O. A. Sofinskaya (Georesursy, 2024)
The study of the influence of technogenesis on the state of surface waters in urbanized areas is one of the most urgent ecological and social problems. For processing and analysis of hydrochemical indicators of surface water bodies of Kazan for the period 2014–2020 the generally accepted stasticial indicators, as well as the methods of multivariate statistics were used. Hydrochemical models were built using the ArcGisMap software package. The data were grouped using the cluster analysis method separately for each hydrological season with the allocation of 6 groups of hydrochemical components in relation to the maximum permissible values. It has been revealed that the minimum technogenic load on the surface waters of the city falls on the spring period. Based on the analysis of the results obtained, an ecological and hydrological assessment of the state of surface waters was carried out. It was showed that the water bodies of Kazan are classified as unfavorable water bodies.